Carbon - Carbon (Elsevier, 2026)
The journal Carbon is an international multidisciplinary forum for communicating scientific advances in the field of carbon-based materials, including low-dimensional carbon-based nanostructures. The journal reports new, relevant and significant findings related to the formation, structure, properties, behaviors, and technological applications of carbons, which are a broad class of ordered or disordered solid phases composed primarily of elemental carbon. These materials can be either synthetic or of natural origin, and include, but are not limited to: carbon black; carbon fibers and filaments; carbon nanotubes; diamond and diamond-like carbon; fullerenes; glassy carbon; graphite; graphene; graphene-oxide; porous carbons; pyrolytic carbon; and other sp2 and non-sp2 hybridized carbon systems.
FI 1.77
Q1
Keywords: Chemistry; Chemical sciences; Ciencias químicas; Acuerdos transformativos; Transformative agreements; Carbono; Comportamiento; Aplicaciones tecnológicas; Estructura; Propiedades